Technology evolution and industry development of 5G + industrial proximity network - Shiying ZHENG; Yuan LI; Bohan YANG; Shuai MA; Shanpeng XIAO (Dianxin kexue)
In recent years, IoT technology had been widely used in new retail, smart logistics, smart parks, smart manufacturing and other industries, including product management based on RFID, equipment data collection based on short-distance communication, equipment remote control based on deterministic transmission, etc.These communication technologies used for equipment connection and data intercommunication were called industrial proximity network.The concept, development history of proximity network was introduced, and demand for the integration of proximity network and cellular network in the digital and intelligent transformation of verticals was analyzed.Then the architecture, technical advantages and development trends of 5G+ industrial proximity network and its typical applications were expounded, which aimed to provide new ideas for the developing of industrial proximity network.